A Systematic Literature Review On The Efficiency Of Heat Reflective Asphalt Pavements To Reduce Urban Heat Islands - Lim, Ewe Loon (Universiti Sains Malaysia, 2022)
More heat is absorbed and stored by asphalt pavements than by natural surfaces. As a result, conventional asphalt pavements emit high temperatures that release heat into the atmosphere and contribute to the phenomenon of urban heat islands (UHI). The livability of the cities is negatively impacted by the rising urban temperature. The temperature of the pavement has a significant impact on the temperature of the air around it, according to earlier studies. A lower pavement temperature will aid in the UHI mitigation efforts because the pavement surfaces make up a sizable portion of the urban fabric. In order to lessen the effects of UHI, cool pavement technologies like heat reflective pavements, which also include the provision of additives and materials, surface coating, and layer design, have been introduced. This systematic literature review (SLR) is primarily concerned with the effectiveness of heat-reflective asphalt pavements in lowering UHI. The various materials and methods used to improve heat reflective ability are also discussed in this SLR. In the meantime, a review of the mechanisms, advantages, and disadvantages of heat reflective pavement was carried out. For a deeper understanding and to serve as a solid foundation for further research in this area, these studies are crucial. To avoid bias and improve the reliability of the data extracted and synthesised, this SLR is planned in accordance with the preferred reporting items for systematic review and meta-analysis (PRISMA). A total of 35 papers are included in this SLR, and cross-referencing links connect them to additional supporting information. The article quality assessment is also being used to avoid publications with poor methodological quality. Systematic searching techniques have been used to weed out irrelevant articles. This review examined the last ten years of pavement engineering research (2012–2022) and may offer suggestions for future researchers looking to maximise the ability of heat-reflective asphalt pavement to reduce UHI effect.